2021
DOI: 10.1016/j.jbc.2021.101392
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis for high affinity binding of α1-acid glycoprotein to the potent antitumor compound UCN-01

Abstract: The α1-acid glycoprotein (AGP) is an abundant blood plasma protein with important immunomodulatory functions coupled to endogenous and exogenous ligand-binding properties. Its affinity for many drug-like structures, however, means AGP can have a significant effect on the pharmokinetics and pharmacodynamics of numerous small molecule therapeutics. Staurosporine, and its hydroxylated forms UCN-01 and UCN-02, are kinase inhibitors that have been investigated at length as antitumour compounds. Despite their potenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Most of the residues identified to be in close contact with fentanyl are found in BB5 of the α 1 -AGP1 polypeptide chain (Table 4). A similar mode of hydrophobic interactions was shown for the α 1 -AGP interaction with a hydroxylated form of staurosporine, UCN-01 [60]. Arginine at position 90 seems to be the key residue stabilizing the hydrophobic interactions of α 1 -AGP with ligands (both for fentanyl and UCN-01) and it was identified as the residue in close contact for all our docking simulations.…”
Section: Interactions Of Fentanyl With Plasma Proteinssupporting
confidence: 76%
“…Most of the residues identified to be in close contact with fentanyl are found in BB5 of the α 1 -AGP1 polypeptide chain (Table 4). A similar mode of hydrophobic interactions was shown for the α 1 -AGP interaction with a hydroxylated form of staurosporine, UCN-01 [60]. Arginine at position 90 seems to be the key residue stabilizing the hydrophobic interactions of α 1 -AGP with ligands (both for fentanyl and UCN-01) and it was identified as the residue in close contact for all our docking simulations.…”
Section: Interactions Of Fentanyl With Plasma Proteinssupporting
confidence: 76%
“…While understanding mechanism of binding of Aripiprazole to AGP was attempted via extrinsic Cotton effects, the magnitudes of the induced circular dichroism did not correlate concluding mechanism of binding of Aripiprazole to this glycoprotein remained unexplained (Nishi et al, 2019). Staurosporine, and its hydroxylated forms UCN-01 and UCN-02, are kinase inhibitors that bind to both AGP1 and AGP2, and though co-crystal of UCN-01 with AGP2 is known, solution NMR suggests ligand binding induced conformational changes which are yet to be delineated for these antitumor compounds 62 . Crystal structure of A variant of AGP bound to UCN01 (PDB ID 7OUB) showed an RMSD of only 0.45 Å over 150 C α residues with another structure of AGP bound to polyglycol (PDB ID 3APU).…”
Section: Docking Profiles Of Small Molecules On Models Of Agpmentioning
confidence: 99%
“…In some cases, it should be noted that the clinical development of several anticancer drugs has been discontinued due to the longer elimination half-life ( t 1/2 ) caused by an overly high affinity for human AGP. For example, during the drug development process, the development of UCN-01, a multikinase inhibitor, was discontinued due to its very high affinity for human AGP, which resulted in a t 1/2 value of several hundred hours in humans and, as a result, failed to provide the expected therapeutic effect. In addition, clinical trials have shown that vismodegib, an inhibitor of hedgehog signaling, also has an overly long t 1/2 , which resulted in it remaining in the plasma for more than 1 week due to its high affinity for human AGP. , Therefore, establishing a rodent animal model that allows the in vivo evaluation of the contribution of AGP in drug pharmacokinetics at an early stage of development would be highly desirable …”
Section: Introductionmentioning
confidence: 99%